Kajian Kerusakan Lingkungan Akibat Kegiatan Pemandian Air Panas di Wilayah Desa Tegalsari, Kecamatan Garung, Kabupaten Wonosobo - Ibrahim, Fardan Yusuf (Journal of Geographical Sciences and Education, 2025)
Tegalsari Village is known for its numerous hot spring sources utilized as bathing tourism attractions. The use of geothermal hot springs has caused environmental pollution affecting both terrestrial and aquatic ecosystems, while information on their impacts and management remains very limited. This study aims to 1) analyze the impact of hot spring bathing activities on terrestrial and aquatic environmental conditions, 2) identify the factors causing environmental degradation, and 3) formulate appropriate management strategies. The research employed a descriptive qualitative method with data collected through observation and interviews. The results indicate that hot spring bathing activities have a significant impact on environmental quality degradation. The main contributing factors are high temperature, low pH, heavy metal content, and anthropogenic activities. The recommended environmental management strategies include planning, control, restoration, and maintenance efforts.